2018
DOI: 10.1515/ijeeps-2017-0250
|View full text |Cite
|
Sign up to set email alerts
|

A Buck-Boost DC/DC Converter with High Efficiency Suitable for Renewable Energies

Abstract: In this paper, a non-isolated buck-boost dc/dc converter with only one switch is presented. The proposed converter consists of one switch in the input side (S), four inductors, four diodes, six capacitors and a capacitor in the output side (Co). In fact, the combination of the inductor, diode and capacitor leads voltage level is increased. Actually, the voltage stress on power switch is decreased for higher power limits at various duty-cycles by combining these components. Therefore, conduction losses can be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Multi-level connection can be used for both single-input DC source and multi-input DC source converters. As shown in Figure 26a, a module composed of inductors, diodes, and capacitors was introduced in [55]. Multi-level buck-boost converters are realized by using this module.…”
Section: Different Ways Of Connectingmentioning
confidence: 99%
“…Multi-level connection can be used for both single-input DC source and multi-input DC source converters. As shown in Figure 26a, a module composed of inductors, diodes, and capacitors was introduced in [55]. Multi-level buck-boost converters are realized by using this module.…”
Section: Different Ways Of Connectingmentioning
confidence: 99%
“…Similar models are discussed in [20], [21], that aim at power converters, integrated high-quality rectifier regulator, and genetic algorithm (GA) with MLI and in [22]- [25] which aims at reducing harmonics from outputs, thereby improving conversion efficiency levels. Extensions to these models are discussed in [26]- [31] which propose use of switched reluctance motor (SRM), neutral point clamped (NPC), dynamic voltage restorer (DVR) topologies, high brightness light emitting diode (HB-LED), and non-isolated buck-boost dc/dc converters. Based on these methods, it can be observed that very few general-purpose optimization models are available for buck-boost converter performance improvement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The isolated converters usually utilize either a high-frequency transformer or a coupled-inductor to provide electrical isolation and to support a high conversion ratio of voltage by designing the turn's ratio of the high-frequency transformer or the coupled-inductor. The bidirectional dc-dc flyback converters, half-bridge and full-bridge converters are some examples of isolated BDCs [2][3][4][5][6][7]. A bidirectional fly-back converter is one of commonly used isolated BDCs due to its simple structure and easy control.…”
Section: Introductionmentioning
confidence: 99%
“…However, the auxiliary clamping circuit used in these topologies will increase the size and cost of the converter. Numerous isolated topologies based on the halfbridge converter [4,5] or full-bridge converters [6,7] have been developed. Most of these converters possess soft-switching features but the need for more switches and driving circuits accompanied by them is their common drawback.…”
Section: Introductionmentioning
confidence: 99%